Routine Imaging or Symptomatic Follow-Up After Resection of Pancreatic Adenocarcinoma - Andel, Paul C M; van Goor, Iris W J M; Augustinus, Simone; Berrevoet, Frederik; Besselink, Marc G; Bhojwani, Rajesh; Boggi, Ugo; Bouwense, Stefan A W; Cirkel, Geert A; van Dam, Jacob L; Djanani, Angela; Dorcaratto, Dimitri; et al. (JAMA surgery, 2025)
IMPORTANCE: International guidelines lack consistency in their recommendations regarding routine imaging in the follow-up after pancreatic resection for pancreatic ductal adenocarcinoma (PDAC). Consequently, follow-up strategies differ between centers worldwide. OBJECTIVE: To compare clinical outcomes, including recurrence-focused treatment and survival, in patients with PDAC recurrence who received symptomatic follow-up or routine imaging after pancreatic resection in international centers affiliated with the European-African Hepato-Pancreato-Biliary Association (E-AHPBA). DESIGN, SETTING, AND PARTICIPANTS: This was a prospective, international, cross-sectional study. Patients from a total of 33 E-AHPBA centers from 13 countries were included between 2020 and 2021. According to the predefined study protocol, patients who underwent PDAC resection and were diagnosed with disease recurrence were prospectively included. Patients were stratified according to postoperative follow-up strategy: symptomatic follow-up (ie, without routine imaging) or routine imaging. EXPOSURES: Symptomatic follow-up or routine imaging in patients who underwent PDAC resection. MAIN OUTCOMES AND MEASURES: Overall survival (OS) was estimated with Kaplan-Meier curves and compared using the log-rank test. To adjust for potential confounders, multivariable logistic regression was used to evaluate the association between follow-up strategy and recurrence-focused treatment. Multivariable Cox proportional hazard analysis was used to study the independent association between follow-up strategy and OS. RESULTS: Overall, 333 patients (mean [SD] age, 65 [11] years; 184 male [55%]) with PDAC recurrence were included. Median (IQR) follow-up at time of analysis 2 years after inclusion of the last patient was 40 (30-58) months. Of the total cohort, 98 patients (29%) received symptomatic follow-up, and 235 patients (71%) received routine imaging. OS was 23 months (95% CI, 19-29 months) vs 28 months (95% CI, 24-30 months) in the groups who received symptomatic follow-up vs routine imaging, respectively (P = .01). Routine imaging was associated with receiving recurrence-focused treatment (adjusted odds ratio, 2.57; 95% CI, 1.22-5.41; P = .01) and prolonged OS (adjusted hazard ratio, 0.75; 95% CI, 0.56-.99; P = .04). CONCLUSION AND RELEVANCE: In this international, prospective, cross-sectional study, routine follow-up imaging after pancreatic resection for PDAC was independently associated with receiving recurrence-focused treatment and prolonged OS.
Keywords: duktální karcinom slinivky břišní; Cross-Sectional Studies; Male; Survival Rate; lokální recidiva nádoru; následné studie; Carcinoma, Pancreatic Ductal; Aged; Prospective Studies; mužské pohlaví; senioři; pankreatektomie; Pancreatic Neoplasms; Follow-Up Studies; Neoplasm Recurrence, Local; lidé; ženské pohlaví; Humans; nádory slinivky břišní; Pancreatectomy; průřezové studie; Female; lidé středního věku; míra přežití; Middle Aged; prospektivní studie